COLLABORATIVE LEARNING AS THE MANIFESTATION OF SOCIOCULTURAL THEORY: TEACHERS’ PERSPECTIVES - Dian Novita; Fabiola Dharmawati Kurnia; Ali Mustofa (Universitas Muhammadiyah Makassar, 2020)
The purpose of the study is to identify the teachers’ barriers in implementing collaborative learning in EFL classrooms. The study was conducted at Universitas Muhammadiyah Sidoarjo with two teachers as the participants. Additionally, the study employed a qualitative research method by using an in-depth interview to obtain the data. The findings of the study showed that it is difficult to assess students in collaborative work activities besides organizing the doings in the approach. To solve the problems, teachers should pay more attention to students’ group performance, the social interaction, and mutual support of each member of the group rather than focus on group productivity and individual performance in assessing the students’ achievement.